JUMLAH KONSUMEN YANG MENGKONSUMSI KOPI ABC BERDASARKAN DATA KUSIONER DAN DIKELOMPOKAN BERDASARKAN UMUR TAHUN 2024 - Deden Hisbuloh; Bagus Hamdi Nandita, Shendy Dwi Setiaji, Teguh Wibowo, Devi Kharisma (CV. Adiba Aisha Amira, 2024)
In this research, we investigate the number of consumers who consume ABC type coffee based on data collected through questionnaires. ABC type coffee was chosen because of its wide popularity among coffee consumers. The research was conducted using a questionnaire survey method as a means of collecting data from a representative sample of the target population. Our questionnaire was specifically designed to explore various aspects related to ABC coffee consumption, including frequency of consumption, preference for certain varieties and brands, location of purchase, as well as the main reasons for choosing the product. The collected data is then analyzed statistically to identify dominant consumption patterns and factors that influence consumer choices. In- depth analysis of the questionnaire results provides a comprehensive picture of ABC coffee consumer profiles, such as their demographics, taste preferences and brand preferences. The results of this research provide valuable insights for coffee producers and retailers to understand market trends and consumer behavior that underlie their purchasing decisions. The implications of these findings can assist in the development of more targeted and effective marketing strategies, as well as increasing brand awareness and satisfaction consumers towards ABC coffee products. In addition, this research can also be a basis for further research that explores the dynamics of the coffee market and the psychological factors behind consumer preferences for certain types of coffee. Thus, this study not only describes the number of consumers who consume ABC coffee, but also provides an understanding deeper into consumer behavior and coffee market dynamics that are relevant to the industry and its research.